Novel porcine-like human G26P[19] rotavirus identified in hospitalized paediatric diarrhoea patients in Ho Chi Minh City, Vietnam. - My, P; Rabaa, M; Donato, C; Cowley, D; Phat, V; Dung, T; Anh, P; Vinh, H; Bryant, J; Kellam, P; Thwaites, G; Woolhouse, M; et al. (2014)
During a hospital-based diarrhoeal disease study conducted in Ho Chi Minh City, Vietnam from 2009 to 2010, we identified four symptomatic children infected with G26P[19] rotavirus (RV)--an atypical variant that has not previously been reported in human gastroenteritis. To determine the genetic structure and investigate the origin of this G26P[19] strain, the whole genome of a representative example was characterized, revealing a novel genome constellation: G26-P[19]-I5-R1-C1-M1-A8-N1-T1-E1-H1. The genome segments were most closely related to porcine (VP7, VP4, VP6 and NSP1) and Wa-like porcine RVs (VP1-3 and NSP2-5). We proposed that this G26P[19] strain was the product of zoonotic transmission coupled with one or more reassortment events occurring in human and/or animal reservoirs. The identification of such strains has potential implications for vaccine efficacy in south-east Asia, and outlines the utility of whole-genome sequencing for studying RV diversity and zoonotic potential during disease surveillance.